2004
DOI: 10.1103/physrevb.70.184202
|View full text |Cite
|
Sign up to set email alerts
|

In situ high-resolution transmission electron microscopy observation of the phason-strain relaxation process in an Al-Cu-Co-Si decagonal quasicrystal

Abstract: Transition process from a rational approximant state, which is regarded as containing a uniform phason strain in a quasicrystalline state, to the quasicrystalline state in the Al-Cu-Co-Si system has been observed by in situ high-temperature high-resolution transmission electron microscopy (HRTEM). The tiling pattern changing with lapse of time in the HRTEM image has been analyzed, and the spatial and temporal variations of the phason field have been deduced. The results show that two types of processes lead th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…For synthetic phasonic waves, subject to prolonged thermalisation, amplitude recovery reveals either stability or decay as a function of time, depending on the gradient of phasonic strain and temperature. Relaxation of phasonic gradients has previously been observed in phason field reconstructions of metallic alloys [32]. We demonstrate that similar processes occur in intrinsic colloidal quasicrystals.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…For synthetic phasonic waves, subject to prolonged thermalisation, amplitude recovery reveals either stability or decay as a function of time, depending on the gradient of phasonic strain and temperature. Relaxation of phasonic gradients has previously been observed in phason field reconstructions of metallic alloys [32]. We demonstrate that similar processes occur in intrinsic colloidal quasicrystals.…”
Section: Discussionsupporting
confidence: 81%
“…This permits distinguishing random tilings from low-defect quasicrystals [29], and identification of domains with uniform phasonic offsets [30,31]. Reconstructions of phason strain distributions are used to observe phasonic relaxation processes in the bulk [32] and at the growth front [26] of metallic quasicrystals. This article presents a detailed discussion of the embedding procedure in the context of intrinsic colloidal quasicrystals.…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that phasonic flips usually are strongly correlated [7]. Furthermore, strain relaxation that leads to the formation of a decagonal quasicrystal in an Al-Cu-Co-Si system is accompanied by complex collective rearrangements of atoms [8]. In general, phasonic modes contribute to thermal vibrations and thereby are important for the thermal properties of a quasicrystal.…”
mentioning
confidence: 99%
“…They reported the relaxation times ranging from 0.3 to 2 ϫ 10 4 s, obeying an Arrhenius temperature dependence with an activation enthalpy of 4 eV and a frequency factor of 4 ϫ 10 21 s −1 . Phason fluctuations or phasonstrain relaxations in Al-Cu-Co decagonal quasicrystals have been observed by Edagawa et al [13][14][15] by in situ highresolution TEM, and characteristic times ranging from 10 to 700 s have been reported at high temperatures of around 1123 K.…”
Section: Introductionmentioning
confidence: 88%